2002
DOI: 10.1016/s0893-133x(01)00403-1
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptide Y (NPY) Y1 Receptor Subtype Mediates NPY-induced Antidepressant-like Activity in the Mouse Forced Swimming Test

Abstract: The present study was undertaken to investigate the possible antidepressant-like effects of neuropeptide Y (NPY)inNeuropeptide Y (NPY) is a 36-amino acid peptide that is widely distributed in the central nervous system (CNS). Intracerebroventricular (ICV) administration of NPY stimulates food intake (Clark et al. 1985;Levine and Morley 1984;Stanley and Leibowitz 1984), modulates cognition (Flood et al. 1987;Redrobe et al. 1999), inhibits neuronal excitability (Colmers and Bleakman 1994) and has anticonvulsant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(136 citation statements)
references
References 51 publications
9
123
1
2
Order By: Relevance
“…NPY itself has been shown to have antidepressant-like activity. Intracerebroventricular injections of NPY or NPY receptor 1 (Y 1 ) agonists significantly reduced immobility time in both the FST (Husum et al, 2000;Stogner and Holmes, 2000;Redrobe et al, 2002a) and LH paradigms (Ishida et al, 2007). However, the role of VGF in depression has not been explored.…”
Section: Vgf In Depression Modelsmentioning
confidence: 99%
“…NPY itself has been shown to have antidepressant-like activity. Intracerebroventricular injections of NPY or NPY receptor 1 (Y 1 ) agonists significantly reduced immobility time in both the FST (Husum et al, 2000;Stogner and Holmes, 2000;Redrobe et al, 2002a) and LH paradigms (Ishida et al, 2007). However, the role of VGF in depression has not been explored.…”
Section: Vgf In Depression Modelsmentioning
confidence: 99%
“…The effect of [D-His 26 ]-NPY on nicotine withdrawal was investigated as this compound, in contrast to NPY, has a low affinity for the Y5 receptor (NPY, Ki of 0.28 nM for Y1, Ki of 1.5 nM for Y5; ]-NPY, Ki of 2.0 nM for Y1, Ki of 34.6 nM for Y5) (Mullins et al, 2001). Activation of the Y5 receptor has been suggested to mediate NPY's sedative effects while NPY's anxiolytic and antidepressant-like effects have been suggested to be mediated via the activation of the Y1 receptor (Ishida et al, 2007;Redrobe et al, 2002a;Sorensen et al, 2004). Experiment 1 and 2 indicated that NPY and [D-His 26 ]-NPY elevated the brain reward thresholds of the saline-treated control rats.…”
Section: Introductionmentioning
confidence: 99%
“…NPY levels in the cerebrospinal fluid of depressed patients are lower than those in schizophrenics or healthy controls Widerlov et al, 1988). In addition, the central administration of NPY has antidepressant-like effects in animal models such as the rat forced swim test (Redrobe et al, 2002a;Stogner and Holmes, 2000) and clinically effective antidepressant treatments (e.g., repeated electroconvulsive shock stimulation and the selective serotonin reuptake inhibitor fluoxetine) elevate central NPY levels in rats (Baker et al, 1996;Heilig et al, 1988;Stenfors et al, 1989). Taken together, the above-discussed studies suggest that NPY attenuates somatic opioid and alcohol withdrawal signs and low levels of NPY may be implicated in the etiology of negative mood states.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical studies have found reduced NPY concentrations in cerebrospinal fluid and plasma from depressed patients and suicide attempters (Westrin et al, 1999;Nilsson et al, 1996;Hashimoto et al, 1996;Gjerris et al, 1992;Widerlöv et al, 1986). Further, in rats as well as mice, NPY induces antidepressant-like behavior following central administration (Redrobe et al, 2002;Stogner and Holmes, 2000;Husum et al, 2000). The rise in hippocampal NPY-LI in FSL animals in the present study may therefore also be of importance to the proposed mood-stabilizing properties of topiramate.…”
Section: Discussionmentioning
confidence: 50%
“…We have previously shown that levels of neuropeptide Y (NPY), a highly conserved 36 amino-acid neuropeptide that is abundantly distributed in mammalian brain (Tatemoto et al, 1982), are reduced in the hippocampus of FSL rats (Husum et al, 2001;Jiménez Vasquez et al, 2000). Furthermore, in rodents and mice, exogenous NPY exerts antidepressant-like activity and modulates anxiety and stress behavior (Redrobe et al, 2002;Stogner and Holmes, 2000;Thorsell et al, 2000;Husum et al, 2000;Heilig et al, 1989). Most clinical studies have found reduced NPY concentrations in cerebrospinal fluid (CSF) and plasma from depressed patients and suicide attempters (Westrin et al, 1999;Nilsson et al, 1996;Hashimoto et al, 1996;Gjerris et al, 1992;Widerlöv et al, 1986).…”
Section: Introductionmentioning
confidence: 99%